The Meaning of Songkok Recca Semiotic Perspective in Nusantara Module Activities for Independent Student Exchange Participants 2 - Meliana Meliana; Andi Tenri Sua; Andi Muh. Taufiq (Universitas Muhammadiyah Enrekang, 2024)
All regions in Indonesia from Sabang to Merauke have different cultures, from dance, music, clothing to handicrafts which have unique characters, identities, symbols and philosophies that are characteristic of each region. Through the Indonesian Independent Student Exchange (PMM) 2 inbound Nusantara Module activity at Padjadjaran University, students from South Sulawesi had the opportunity to introduce one of the cultural heritages owned by the Bugis Bone tribe, namely songkok recca as an identity or marker for men. This research aims to determine the meaning contained in songkok recca in Bone district in relation to the strata or social status of the Bugis community in Bone district. Research that utilizes a qualitative approach to data collection is obtained from sources or informants who are Bone Regency cultural figures, as well as Songkok Recca craftsmen. Songkok recca is a symbol of power which can be seen from the material of the songkok breaker which is made of pure gold. There are rules for those who wear songkok recca, each of which is seen from the social strata such as nobles, children of kings, slaves and servants.